2011
DOI: 10.1016/j.jss.2009.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Effects of FK506 on the Apoptosis of Hepatocytes and Infiltrating Lymphocytes in an Allografted Rat Liver

Abstract: Background. The current study investigated whether FK506 (FK) regulates the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…TAC functions largely by repressing T cell cytokine gene transcription. TAC also enhances the apoptosis of activated T cells in vivo [28]. Consistent with previous studies, our results showed that TAC suppressed acute rejection after LTx and improved survival time, histopathological changes and blood chemistry data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…TAC functions largely by repressing T cell cytokine gene transcription. TAC also enhances the apoptosis of activated T cells in vivo [28]. Consistent with previous studies, our results showed that TAC suppressed acute rejection after LTx and improved survival time, histopathological changes and blood chemistry data.…”
Section: Discussionsupporting
confidence: 92%
“…NFAT could bind the promoter of IL-2 in activated T cells as a nuclear factor [28]. The mechanism of NFAT activation was discovered indirectly during researches of the mechanism of the immunosuppressive drug cyclosporine.…”
Section: Discussionmentioning
confidence: 99%
“…CsA has demonstrated anti‐apoptotic activity in vitro and in vivo , and reports have suggested that CsA may protect against Fas‐mediated apoptosis in vivo . While initial in vitro evidence suggested tacrolimus did not have an anti‐apoptotic effect , more recent data suggest it may be anti‐apoptotic , indicating the need for further study to investigate whether the potential anti‐apoptotic effects of CsA represent a viable hypothesis for the differences in fibrosis outcomes in patients receiving CsA or tacrolimus.…”
Section: Effect Of Cnis On Fibrogenesismentioning
confidence: 59%